(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This research undertakes a critical re-examination of Marxist theory in the context of the contemporary information technology revolution. The findings of this study reveal that the emergence of digital technology has given rise to novel forms of alienation, power dynamics, control, commodification, and class struggle. Building upon the core Marxist critique of worker alienation, this research employs Critical Discourse Analysis (CDA) to illuminate the ways in which the digital age has exacerbated worker alienation. Specifically, the analysis highlights the role of algorithm-based control, the erosion of social relations through remote working, and the rigid standards imposed on workers as contributing factors to this phenomenon. Furthermore, the commodification of personal data and its utilisation in informing employment and consumer behaviour decisions have intensified surveillance and reinforced capitalist control over labour. The study also finds that the digital age has widened the class struggle, as large tech companies have disproportionately benefitted from the information technology revolution. However, this research also identifies the emergence of emancipatory potential, as online communities and collective organising efforts have created opportunities for resistance and challenge to capitalist powers. As these efforts continue to evolve, they may ultimately erode the undue power and control held by the capitalist class.